Efektivitas Pengelolaan Sampah Organik dengan Pencacah dan Kolaborasi Bank Sampah - Wulansari, Nofita; Lathifa Haryati, Fidela; Prima Andini, Puspa; Salsabila, Sabrina; Jeremy Ryan, Benedictus; Mandasari, Virginia (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
This community service research aims to enhance the awareness, knowledge, and skills of residents in Margorejo Urban Village in independently managing household organic waste by utilizing simple technology in the form of a waste shredder. The main issue addressed is the low level of waste sorting and organic waste management practices at the household level, which contributes to high waste volume and suboptimal utilization of organic waste. The activities were carried out using a participatory approach, through direct observation and semi-structured interviews. The stages included community outreach, technical training on the use of the organic waste shredder, and assistance in composting practices involving the local waste bank as a partner. This collaborative approach enabled direct knowledge transfer and fostered a sense of ownership in environmental management. The results show that the use of the waste shredder accelerated the composting process, significantly reduced waste volume, and increased community participation in sustainable waste management efforts. Furthermore, the involvement of the waste bank strengthened local networks in integrated waste management and supported the implementation of circular economy principles in urban communities. In conclusion, the integration of a waste shredder and collaboration with a waste bank has proven effective in encouraging behavioral changes towards independent and sustainable waste management. This model can be replicated in other areas with similar conditions as a practical and applicable solution to address organic waste issues.